THE INFLUENCE OF HALAL PRODUCT KNOWLEDGE, HALAL LABELING, AND RELIGIOSITY ON THE PURCHASE DECISION OF HALAL FOOD AT SFA STEAK & RESTO (SFA HALAL FOOD) GENTAN - Dewi Ermawati; Sri Walyoto (UIN Raden Mas Said Surakarta, 2024)
This study aims to analyze the influence of product knowledge, halal labeling, and religiosity on purchasing decisions for halal food at SFA Steak & Resto (SFA Halal Food) Gentan. The research focuses on millennials born between 1980 and 2000, aged 23-43 years, residing in Sukoharjo, who have made purchases, with an unknown population size. Data analysis was conducted using multiple linear regression with a sample size of 100 respondents. The sample size proportionally represents each sub-district in Sukoharjo. The sampling technique employed was non-probability sampling with purposive sampling. Data was collected through questionnaires. The type of data used is cross-sectional data, obtained from primary and secondary sources. The results of the study indicate that product knowledge, halal labeling, and religiosity simultaneously influence purchasing decisions. The development of religiosity and the implementation of strategies using AI and ML algorithms are suggested for further application.